GrainSafe Dryer and hermetic rice storage system for South-Eastern Asia, Southern Asia and Western Africa - CGIAR Research Program on Rice (2021)
The GrainSafe with 1t capacity was tested at IRRI. The drying principle (in-store drying) has been researched thoroughly over 7 years. The first commercial prototype is being piloted with national partners in 6 countries. A drying simulation program is being developed. This is successfully piloted in Vietnam In 2021.